A qualitative study on the impact of globalisation on public relations practice in Ghana - Albert Anani-Bossman; Michael Bruce (Communicare)
The article analyses the perceived impact of globalisation on public relations practice in Ghana by examining how Ghanaian PR practitioners are utilising the opportunities that globalisation offers while dealing with the challenges it brings. The qualitative interview technique was used to interview a total of five (5) PR practitioners from the non-banking financial services sector. Results show PR practitioners are very much aware of the demand placed on them by globalisation. Communication infrastructural challenges as well as a lack of technological skills is proving a huge challenge in the management of communication activities. As multinational organisations continue to flood into the country, the competition will be keen. Practitioners need to upgrade their skills, especially in the area of digital communication, and knowledge regarding the current standards of practice in the era of globalisation. It is essential for PR educators in Ghana to respond to the challenge of globalisation by redefining their teaching curriculums to reflect the dynamics of international practice. Moreover, it is time for African PR scholars to make a significant contribution to this discussion from an African perspective. The limited number of interviewees and the selection of practitioners from a particular sector of the economy, however, means the research cannot be generalised.